Peran Keadilan Distributif, Keadilan Prosedural dan Keadilan Interaksioal Terhadap Komitmen Afektif Karywan PT G&N Woods Craftindo - Fuzi Kawaibi; Dedi Junaedi; Faisal Salistia (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The following research discusses the role of distributive justice, procedural justice and interactional justice on affective commitment. Both procedural justice, distributive justice and interactional justice can be a factor in the occurrence of affective commitment to employees of PT G&N WOODS CRAFTINDO. The population of this research is all employees of the company with a total of 43 employees, in which the sampling uses a saturated sample. The data collection technique used in this research is a questionnaire or also called a questionnaire. The test instrument used in this research is the validity test and the reliability test. The data analysis technique used in this research is descriptive analysis, classical assumption test, normality test, multicollinearity test, heteroscedasticity test. Test of linear regression analysis, hypothesis testing used in this research is t test and f test. And the results of this study indicate that distributive justice, procedural justice, and interactional justice have a positive and significant effect on employees' affective commitment. Keywords: Distributive Justice, Procedural Justice, Interactional Justice and Affective Commitment